(untitled) (Povijesni prilozi (Historical Contributions), 2019)
The paper shows how Maria Th eresa’s legacy was remembered and highlighted already in the late 19th century within the realm of musical culture. Focusing on the genre of operetta and taking The Gypsy Baron (1885) by Johann Strauss II (1825-1899) as an example the paper touches upon the issues of propaganda and collective memory as conjured up by musical theatre. Considered ‘a musical monument to the Austro-Hungarian Empire’ The Gypsy Baron (originally Der Zigeunerbaron) ultimately reveals the position the “King” Maria Th eresia cherished in the 19th century Empire, being at the same time a fine example of the legacy of her politics. The pillars of the operetta’s plot are wars fought by Austrians: the Austro–Turkish War and the War of the Austrian Succession (1740-1748). The operetta is clearly the work inscribed into the specific political situation of the late 19th century and constituted a musical response to concrete needs stimulated by civil attitudes. Hence the situation depicted in The Gypsy Baron reflects the multi-ethnic diversity of Habsburg Empire and the operetta’s overall message is to glorify the cooperation between various nations as (supposedly) facilitated under Maria Theresa’s reign.